METHODOLOGICAL APPROACHES TO ASSESSING THE IMPACT OF MARKETING INSTRUMENTS ON THE ECONOMIC SECURITY OF AN ENTERPRISE (Development Service Industry Management, 2023)
The article actualises a necessity and develops methods of assessment of influence of marketing instruments upon economic security of enterprise. The essence of the optimal level of the marketing component of the economic security of enterprise has been determined, which is the basis for applying the proposed methodology. The groups have been specified and quantitative and qualitative indicators within each group have been outlined in order to form a methodology for assessing the impact of marketing instruments on the economic security of enterprise. Thus, it is proposed to form indicators within groups that reveal the features of the "4 P's" complex, namely: "Product", "Price", "Distribution Channels", "Market Place", which in fact are the main instruments that directly affect the economic security of enterprise. Given that marketing is one of the most progressive and dynamic economic spheres, which requires the use of modern approaches to its research, the article substantiates the expediency of applying the approaches of integrated digital marketing audit in the formation of a methodology for assessing the impact of marketing tools on the economic security of an enterprise. The author's own structural and logical model of marketing instruments that affect the economic security of enterprise is presented. To determine the level of the marketing component of economic security, it is proposed to use the method of weighted sum, which involves taking into account the weight of each group and individual indicators of the economic security component and their scoring. A scale for interpreting the obtained results has been developed and measures of supporting or active direction to adjust the impact of marketing instruments on the economic security of enterprise have been identified. At the same time, supportive measures should be used at all times, provided that the level of the marketing component of economic security is acceptable, at which the marketing activities of the enterprise are effective and contribute to the adaptation of the business entity to the conditions of the business environment in which it operates. Active measures will be anti-crisis in nature and should be used when there are signs of a deepening crisis in the marketing sphere, which significantly affects the marketing component of the economic security of the enterprise.
Keywords: marketing instruments; marketing component of economic security of enterprise; methodology for assessing the impact of marketing instruments on the economic security of enterprise; optimal level of the marketing component of economic security of enterprise; digital marketing audit